2020
DOI: 10.1177/0265532220911626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prompt type on test-takers’ writing performance and writing strategy use in the continuation task

Abstract: The continuation task, a new form of reading-writing integrated task in which test-takers read an incomplete story and then write the continuation and ending of the story, has been increasingly used in writing assessment, especially in China. However, language-test developers’ understanding of the effects of important task-related factors on test-takers’ performance with regard to this task is still in its infancy. In this study we investigate the effect of prompt type on English as a foreign language (EFL) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…It was employed in this study particularly because it was implemented in one of the largest English tests for EFL learners, and it also overlapped with some widely accepted theoretical frameworks (Ellis, 2008). It was also widely used as an analytical instrument in L2 writing studies (Shi et al, 2020).…”
Section: Instrumentmentioning
confidence: 99%
“…It was employed in this study particularly because it was implemented in one of the largest English tests for EFL learners, and it also overlapped with some widely accepted theoretical frameworks (Ellis, 2008). It was also widely used as an analytical instrument in L2 writing studies (Shi et al, 2020).…”
Section: Instrumentmentioning
confidence: 99%
“…Four groups of Chinese EFL learners participated in a continuation task with four different prompts, namely, bare prompt, framed prompt, vocabulary prompt, and framed vocabulary prompt [4]. Results showed that the more complex prompt type significantly improved the participants' overall writing scores, syntactic complexity, cohesion, as well as source-use features [4]. Thus, their study confirmed that a more complex prompt type stimulates a better writing performance.…”
Section: Introductionmentioning
confidence: 75%
“…This can be illustrated as the ratio of the number of content words to the total number of words, the proportion of relatively unusual or advanced words, and the range of a learner's vocabulary as displayed in a text [19]. However, when it comes to the quantification of lexical complexity in the specific writing task, four indices from Coh-Metrix were adopted in a recent study concerning the effect of prompt type, namely MTLD (Measure of Textual Lexical Diversity), Incidence of content words (i.e., the sum of noun incidence, adverb incidence, adjective incidence, and verb incidence per 1,000 words), WRDCacwm (mean concreteness for content words) and WRDlacwm (mean imageability for content words) [4].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations